Meerkat polarimetric observations of Pictor A - Andati, Lexy Acherwa Livoyi (Rhodes University, Faculty of Science, Department of Physics and Electronics)
Pictor A is one of the brightest and closest radio galaxies in the Southern Hemisphere, offering a unique opportunity for in-depth studies of the astrophysics of radio galaxies and their interactions with their environments. Many multi-wavelength studies of this source have been done. However, the most comprehensive radio frequency study of Pictor A's morphological components was conducted by Perley et al. (1997) using the Very Large Array (VLA) located in the Northern Hemisphere. To date, that work remains the most detailed study of Pictor A. In this thesis, we conducted a spectropolarimetric study of Pictor A using new L-band data obtained in 2019 from the high-sensitivity MeerKAT telescope, which provides the deepest and most sensitive data of this source at a continuous and finely sampled frequency coverage in the L-band. Thus, due to Pictor A's proximity, high luminosity, and the MeerKAT's high sensitivity, the data delivers a unique dataset for our study of the magnetic field structure of Pictor A and allows for a detailed study of the source's morphological structures. We presented the steps taken during our calibration and data reduction, leading to polarimetryready images. During the first phase of calibration, excision of data corrupted by instrumental effects and radio frequency interference (RFI) resulted in only 50% useable data. Pictor A's exceptionally bright western hotspot introduced significant artefacts in our images, mitigated in the second calibration phase through direction-dependent calibration. The calibrated data resulted in a multi-frequency syn
Keywords: Polarimetry; MeerKAT; Radio astronomy; Radio galaxies; Cosmic magnetic fields; Pictor A